Thursday, 14 June 2018: 2018
DOI: 10.1136/annrheumdis-2018-eular.2404
|View full text |Cite
|
Sign up to set email alerts
|

THU0304 Association of anxiety, depression and fatigue with disease activity, joints erosion and skin lesion severity in early psoriatic arthritis patients

Abstract: BackgroundDepression is one of the precursors of psoriasis and psoriatic arthritis (PsA) development. It was found that depression and anxiety negatively affect the achievement of remission in PsA. B. Michelsen 2017] Interrelation of anxiety, depression and fatigue (according to patient-reported outcomes) with disease activity, erosive arthritis and skin lesion severity in early PsA hadn’t been sufficiently studied.ObjectivesTo study anxiety, depression and fatigue disorders (according to patient-reported outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…1). Ultimately, 66 of the 84 studies were excluded from inclusion in the systematic literature review (Table 1) [12,, and 18 articles were included [9,14,[83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98], one of which had been identified from the hand search (see Tables 2 and 3 for more detail).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1). Ultimately, 66 of the 84 studies were excluded from inclusion in the systematic literature review (Table 1) [12,, and 18 articles were included [9,14,[83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98], one of which had been identified from the hand search (see Tables 2 and 3 for more detail).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies included in the systematic literature review were cross-sectional [9,84,85,[87][88][89][90][92][93][94][95][96][97], although prospective observational studies were also found [14,83,86,91,98], and most were of moderate quality (predominantly Oxford CEBM levels of evidence 2b or 4). The total number of PsA patients included in each study ranged from 3571 [91] to 40 [97].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations